E-referrals: improving the routine interspecialty inpatient referral system. Issue 3 (28th September 2018) - Shephard, Emma; Stockdale, Claire; May, Felix; Brown, Alistair; Lewis, Hannah; Jabri, Sara; Robertson, Daniel; Moss, Victoria; Bethune, Rob
Abstract : Interspecialty referrals are an essential part of most inpatient stays. With over 130 referrals occurring per week at the Royal Devon and Exeter Hospital, the process must be efficient and safe. The current paper-based 'white card' system was felt to be inefficient, and a Trust incident highlighted patient safety concerns. Questionnaires reinforced the need for improvement, with concerns such as a lack of referral traceability and delays in the referral delivery due to workload. The aims of the project were to improve patient safety and junior doctor efficiency in the referral process. Through appreciative enquiry and the PDSA (Plan-Do-Study-Act) model, an electronic referral system was developed, piloted within two specialties and later expanded to others with improvements made along the way based on user feedback. The system includes novel features including specialties 'acknowledging' a referral to allow referral progress to be tracked. The system stores all referrals, creating a fully auditable inpatient referral pathway. Qualitative data indicated improvement to patient safety and user experience (n=31). Timings for referrals were measured over a 6-month period; referrals became faster with the electronic system, with average time from decision to refer to referral submission improving from 2.1 hours to 1.9 hours, with a noted statistically significant improvement in timings on a statistical process control chart. An unexpected benefit was that patients were also reviewed faster by specialties. Measuring these changes presented a significant challenge due to the complexity of the referral process, and this was a big limitation. Overall, the re-design of a paper-based referral system into an electronic system has been proven to be more efficient and felt to be safer for patients. This is a sustainable change which is being rolled out Trust-wide. We hope that the reporting of this project will help others considering reviewing their inpatient referral pathways.